THE ROLE AND IMPORTANCE OF USING DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF CREATIVITY OF FUTURE TECHNOLOGY TEACHERS - Bahronova Shaxlo Islom qizi; Davlatova Nasiba Ubaydillayevna (PEDAGOGS, 2024)
Abstract: this article shows the role and importance of using digital technologies in the development of creativity of future technology teachers. In addition, the factors of development of the creative component and the concept of this creativity are given briefly.